Accounting for the numberphobic : a survival guide for small business owners - Fotopulos, Dawn (AMACOM/American Management Association, 2015)
Without a working knowledge of their financial statements, small-business owners' have no hope of success. Demystifying a company's financial dashboard (the Net Income Statement, Cash Flow Statement, and Balance Sheet), Accounting for the Numberphobic explains in plain English how each measurement impacts decisions, and reflects the overall health of any business. Readers will discover what the balance sheet reveals about their company's worth; how to identify the break-even point that means a business is self-sustaining; how the Net Income Statement can help grow profits; how to maximize cash.